Using Cover Crops to Suppress Weeds and Improve Soil Health - J. A. Dille; L. I. Chism; G. F. Sassenrath (Kansas Agricultural Experiment Station Research Reports, 2021)
Herbicide-resistant weeds are creating challenges for producers to control weeds in crop fields. This study explores the potential of cover crops to reduce weed pressure and improve soil health. Cover crops were planted after corn harvest in tilled and no-till fields, and included Graza radish, winter wheat, annual ryegrass, spring oats, winter oats, and forage collards. The control was fallow with herbicide application but no cover crop. Soil health was determined prior to cover crop termination. Graza radish and forage collards did not grow consistently in all plots due to poor germination and winter kill. Significant weed biomass was produced in the fallow plot or in plots with poor cover crop stands. Microbial biomass was much greater in the no-till field than in the tilled fields.
Keywords: cover crops; weed management; soil health